Flat Design Sebagai Gaya Visual Perancangan Asset Bangunan Pada Web “Peta Interaktif” - Fadjar Satria Dwi Putra; Alfian Candra Ayuswantana (Journal of Creative Student Research, 2023)
Creating a digital "interactive map" web is one of the uses of current technological developments. However, to create an attractive website, it also needs a good design. One of them is by creating an asset environment. The aim of this research is to describe the form of design for buildings such as houses, buildings and places of worship using a flat design visual style which will later be used as an asset on the "interactive map" web. The method used in this research is a qualitative method to describe all forms of the design process. Apart from that, the author also implements the stages of art creation according to Gustami (2007), starting from idea exploration to the design process. From the research results, there are several stages that need to be carried out in creating a building design, namely looking for references, forming initial patterns using tools on the Figma platform, to the detailing process so that the image looks more realistic. The creation of environmental assets in the form of buildings will be applied to an "interactive map" web as a visual complement to make it more attractive and many people are interested in accessing the website.